PENGARUH PARITAS INDUK TERHADAP PERTAMBAHAN BOBOT BADAN ANAK BABI SELAMA MASA LAKTASI PADA PETERNAKAN RAKYAT DI GUNUNG NONA KOTA AMBON - Helena Latale; Demianus Ferdinand Souhoka; Jeffrie Wattimena (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This research investigated the effect of sow parity on piglet growth performance during the lactation period in smallholder pig farms in Gunung Nona, Ambon. Fifteen sows representing parity 1, 2, and 3 were monitored from farrowing to weaning ( 35 days). Observed variables included birth weight, weaning weight, average daily gain (ADG), mortality, and production efficiency. Results indicated that parity-2 sows produced piglets with the highest birth and weaning weights and the greatest mean ADG (0.15 kg/day), while pre-weaning mortality remained low (1.94%). Statistical testing revealed significant differences among parities for ADG. These findings suggest that mid-parity sows offer optimal physiological conditions for lactation in smallholder systems. Management recommendations include implementing parity-specific feeding and lactation strategies to improve productivity and efficiency.